A new species in the genus Chadisra Walker (Notodontidae: Periergosinae) from the Great Nicobar Island, India - Singh, Navneet; Ahmad, Jalil; Raha, Angshuman (Zootaxa, 2021)
A new species, Chadisra curvipenis N. Singh, Ahmad & Raha, sp. nov. is described from the Great Nicobar Island, India, and its detailed description along with habitus images, male genitalia illustrations and diagnoses with similar congeners are provided. A complete checklist of the genus with distributional records and a distribution map are given.